Application of Pyrene Fluorescence to the Characterization of Hydrophobically Modified Starch Nanoparticles - Kim, Damin; Amos, Ryan; Gauthier, Mario; Duhamel, Jean (American Chemical Society, 2018)
Several aspects of pyrene fluorescence were applied to gain an insight into the nature of the microdomains in hydrophobically modified starch nanoparticles (HM-SNPs), prepared by reacting SNPs with propionic and hexanoic anhydride to yield C3- and C6-SNPs, respectively. The fluorescence experiments took advantage of the inherent hydrophobicity of pyrene to bind onto the hydrophobic domains generated by the HM-SNPs, and its specific response to the polarity of its environment, to probe its accessibility to quenchers such as oxygen or nitromethane dissolved in water. The equilibrium constant KB for the binding of pyrene onto HM-SNPs, the ratio (I1/I3)o describing the relative hydrophobicity of the microenvironment experienced by pyrene, its lifetime (τSNP), and the rate constant of quenching of pyrene bound to the HM-SNPs by water-soluble nitromethane (kqSNP) were determined as a function of the degree of substitution and weight fraction (wt %) of the hydrophobic modifier. The C3- and C6-SNPs yielded similar parameters at low levels of hydrophobic modification, indicating higher hydrophobicity of the modified SNPs with increasing modification level. However, SNPs modified with more than 5 wt % of hexanoyl pendants all displayed enhanced hydrophobicity for the C6-SNPs relative to the C3-SNPs. This substantial enhancement is attributed to the formation of larger hydrophobic microdomains by the hexanoyl pendants of the C6-SNPs above the 5 wt % C6-modification threshold, which did not occur with the C3-SNPs. Finally, the size of the SNPs did not appear to influence their relative hydrophobicity. These experiments demonstrate how the fluorescence of pyrene can be harnessed to provide information about the relative hydrophobicity of HM-SNPs.
This document is the Accepted Manuscript version of a Published Work that appeared in final form in LANGMUIR, copyright © American Chemical Society after peer review and technical editing by publisher. To access the final edited and published work see https://doi.org/10.1021/acs.langmuir.8b01591.
Keywords: starch nanoparticles, hydrophobic modification, pyrene, fluorescence